ANALISIS OPTIMASI QUERY PADA DATA MINING - Ermatita - (Jurnal Sistem Informasi, 2009)
Data mining is currently being used by organizations or companies to dig up information from the data that the data has been collected in a time long enough and in large numbers.To process a large amount of data in need of a strategy that can make processing data in an effective and efficient. Query optimization is a strategy or the way that can be used inthe initialization and data processing in order to get the results of queries that is effective and efficient. Query optimization approach to rule-based and cost-based that can generate the required information quickly and accurately.